REPRODUCTIVE HORMONES AND CORTISOL RESPONSES TO PLYOMETRIC TRAINING IN MALES - Serife Vatansever Ozen (Biology of Sport, 2012)
Plyometric training activities are commonly used by a wide range of athletes to increase jump performance and improve explosive power and muscular activation patterns. The purpose of the study was to evaluate the effects of plyometric training on male reproductive hormones. Nineteen recreationally active males volunteered to participate in this study and were randomly assigned to plyometrically trained (n=10, 21.2 ±2.3 years) and control groups (n=9, 21.4± 2.1). The plyometric training group performed in a six-week plyometric training programme and the control group did not perform any plyometric training techniques. Resting serum levels of testosterone, prolactin, follicle stimulating hormone (FSH), luteinising hormone (LH), and cortisol were measured in each subject at t0 (before the training), t1 (end of third week) and t2 (end of training). Two-way ANOVA revealed significant (P<0.05) interaction effects for testosterone, prolactin, FSH and cortisol. Six-week plyometric training decreased serum levels of testosterone, cortisol and FSH and increased serum levels of prolactin. These results suggest the presence of alterations in anabolic and catabolic hormonal responses to resistance exercise in men.